Age-Dependent in vitro Maturation Efficacy of Human Oocytes – Is There an Optimal Age? - Karavani, Gilad; Wasserzug-Pash, Peera; Mordechai-Daniel, Talya; Bauman, Dvora; Klutstein, Michael; Imbar, Tal (Frontiers in Cell and Developmental Biology, 2021)
In vitro maturation of oocytes from antral follicles seen during tissue harvesting is a fertility preservation technique with potential advantages over ovarian tissue cryopreservation (OTC), as mature frozen and later thawed oocyte used for fertilization poses decreased risk of malignant cells re-seeding, as compared to ovarian tissue implantation. We previously demonstrated that in vitro maturation (IVM) performed following OTC in fertility preservation patients, even in pre-menarche girls, yields a fair amount of oocytes available for IVM and freezing for future use. We conducted a retrospective cohort study, evaluating IVM outcomes in chemotherapy naïve patients referred for fertility preservation by OTC that had oocyte collected from the medium with attempted IVM. A total of 133 chemotherapy naïve patients aged 1–35 years were included in the study. The primary outcome was IVM rate in the different age groups – pre-menarche (1–5 and ≥6 years), post-menarche (menarche-17 years), young adults (18–24 years) and adults (25–29 and 30–35 years). We demonstrate a gradual increase in mean IVM rate in the age groups from 1 to 25 years [4.6% (1–5 years), 23.8% (6 years to menarche), and 28.4% (menarche to 17 years)], with a peak of 38.3% in the 18–24 years group, followed by a decrease in the 25–29 years group (19.3%), down to a very low IVM rate (8.9%) in the 30–35 years group. A significant difference in IVM rates was noted between the age extremes – the very young (1–5 years) and the oldest (30–35 years) groups, as compared with the 18–24-year group (p < 0.001). Importantly, number of oocytes matured, percent of patients with matured oocytes, and overall maturation rate differed significantly (p < 0.001). Our finding of extremely low success rates in those very young (under 6 years) and older (≥30 years) patients suggests that oocytes retrieved during OTC prior to chemotherapy have an optimal window of age that shows higher success rates, suggesting that oocytes may have an inherent tendency toward better maturation in those age groups.